Fixation failure in patients with traumatic diastasis of pubic symphysis: impact of loss of reduction on early functional outcomes - Claudio Rojas; Ernesto Ewertz; Jose Miguel Hormazábal (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Failure of fixation (FF) in pubic symphysis diastasis (SD) ranges between 12 and 75%, though whether it influences functional outcomes is still debated. The objective of this study is to evaluate the impact of anterior pelvic plate failure and loss of reduction on Majeed’s functional scores. Methods Single center retrospective review of consecutive patients with acute SD treated by means of anterior pubic plating. Thirty-seven patients with a mean age 45.7 ± 14.4 years were included. Demographics, AO classification, pelvic fixation and secondary procedures were recorded. Majeed’s functional scores at minimum 6 months follow-up were compared according to the presence of FF and loss of reduction. Results Fifteen patients presented FF. Eight presented an additional loss of symphyseal reduction. Mean Majeed´s score (MMS) in patients with and without FF was 64.4 ± 13.04 and 81.8 ± 15.65, respectively (p = 0.0012). Differences in MMS in patients without FF and those with FF and maintained or loss of anterior reduction were 11.3 [70.5 vs 81.8] (p = 0.092) and 22.7 [59.1 vs 81.8] (p = 0.001), respectively. Significant association of FF with AO classification was noted. (OR 12.6; p = 0.002). Conclusions Differences in MMS in the analyzed groups suggest that loss of reduction might be more relevant than failure of the anterior osteosynthesis in functional outcomes.